Health Promotion for the Prevention of Extraordinary Events or Outbreaks: A Systematic Review - Katmini, Katmini; Inayatun Nazliyah (Journal of Applied Nursing and Health, 2024)
Background: Health promotion is key in dealing with extraordinary events or outbreaks. This approach empowers the public to understand disease risks, adopt preventive behaviors, and improve compliance with health protocols. Various health promotion interventions have been implemented in recent decades to deal with outbreaks such as dengue fever, influenza, and the COVID-19 pandemic. However, a systematic study is still needed to evaluate the strategies' effectiveness and identify existing challenges and opportunities. This study aims to systematically assess the role of health promotion in managing outbreaks, focusing on best practices, barriers, and opportunities for implementation. Methods: This study uses a systematic review method by following the guidelines of PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses). Data is obtained from major databases, such as Google Scholar, Science Direct, and PubMed. Article searches were carried out systematically from 2019-2024 using several keywords, namely " Health Promotion ", or " Extraordinary Events ", or " Outbreaks ". The selection process includes identifying, screening, selecting, and analyzing articles based on predetermined inclusion and exclusion criteria Results: Of the 2,000 articles identified, 45 met the inclusion criteria. Furthermore, it was selected into the 10 best articles by the author. The results showed that health promotion effectively increased public awareness, changed behavior, and prevented disease spread. Community-based interventions, digital media campaigns, and the involvement of local figures have proven successful. However, obstacles such as low health literacy, cultural resistance, and limited resources are still the main obstacles.. Conclusion: Health promotion has a significant role in preventing outbreaks. An integrated, adaptive, evidence-based approach to local contexts involving multiple stakeholders is needed to improve its effectiveness. By addressing existing challenges, health promotion can be a key pillar in preventing and dealing with future outbreaks